Broad Genomic Sampling Reveals a Smut Pathogenic Ancestry of the Fungal Clade Ustilaginomycotina. (15th May 2018) - Kijpornyongpan, Teeratas; Mondo, Stephen J; Barry, Kerrie; Sandor, Laura; Lee, Juna; Lipzen, Anna; Pangilinan, Jasmyn; LaButti, Kurt; Hainaut, Matthieu; Henrissat, Bernard; Grigoriev, Igor V; Spatafora, Joseph W; et al.
Abstract: Ustilaginomycotina is home to a broad array of fungi including important plant pathogens collectively called smut fungi. Smuts are biotrophs that produce characteristic perennating propagules called teliospores, one of which, Ustilago maydis, is a model genetic organism. Broad exploration of smut biology has been hampered by limited phylogenetic resolution of Ustilaginiomycotina as well as an overall lack of genomic data for members of this subphylum. In this study, we sequenced eight Ustilaginomycotina genomes from previously unrepresented lineages, deciphered ordinal-level phylogenetic relationships for the subphylum, and performed comparative analyses. Unlike other Basidiomycota subphyla, all sampled Ustilaginomycotina genomes are relatively small and compact. Ancestral state reconstruction analyses indicate that teliospore formation was present at the origin of the subphylum. Divergence time estimation dates the divergence of most extant smut fungi after that of grasses (Poaceae). However, we found limited conservation of well-characterized genes related to smut pathogenesis from U. maydis, indicating dissimilar pathogenic mechanisms exist across other smut lineages. The genomes of Malasseziomycetes are highly diverged from the other sampled Ustilaginomycotina, likely due to their unique history as mammal-associated lipophilic yeasts. Despite extensive genomic data, the phylogenetic placement of this class remains ambiguous. Although the sampled Ustilaginomycotina members lack many core enzymes for plant cell wall decomposition and starch catabolism, we identified several novel carbohydrate active enzymes potentially related to pectin breakdown. Finally, ∼50% of Ustilaginomycotina species-specific genes are present in previously undersampled and rare lineages, highlighting the importance of exploring fungal diversity as a resource for novel gene discovery.